Local residents’ attitudes toward and contact with international students: a perspective from Montreal, Quebec - Tekin, Oguzhan; Trofimovich, Pavel (Frontiers in Psychology, 2024)
As migrants holding temporary, foreign-resident status in their host communities, international students often experience prejudice and have little meaningful contact with locals. To date, a comprehensive account of international students' experience is lacking, and existing conceptualizations exclude linguistic threat as a potential source of increased prejudice and diminished contact. Therefore, our goal in this study (set in Quebec, Canada) was to explore local residents' attitudes toward and contact with international students in relation to five potential threats experienced by local residents, including cultural differences, competition over resources, intergroup anxiety, stereotypes, with linguistic threat added as a new, previously unexplored variable. We recruited 59 student and non-student local francophone residents as participants and examined their attitudes toward, perceptions of threat from, and the quality and quantity of contact with international students attending English-medium universities. Both student and non-student participants demonstrated positive attitudes toward and low levels of perceived threat from international students, except for linguistic threat. Compared to student participants, non-student participants reported significantly greater linguistic threat from international students and described contact with them that was both less frequent and lower in quality. Regression models accounted for 50-67% of variance in participants' attitudes, with symbolic threat to social values and belief systems emerging as the common significant predictor of attitudes for both groups. Adding linguistic threat did not improve regression models. Finally, only contact quality showed significant relationships with attitudes and perceived threat, where greater contact quality was associated with more favorable attitudes and reduced threat. We discuss implications of intergroup attitudes and contact for language planning and use in multilingual contexts.